OPTIMISED UNIT COMMITMENT AND DYNAMIC ECONOMIC DISPATCH FOR LARGE SCALE POWER SYSTEMS - Ab Ghani, Mohd Ruddin (1989)
This thesis deals with the unit commitment and dynamic economic dispatch problems for large scale power systems. The secure dynamic economic dispatch problem was modelled to cater for many physical and system operational constraints. By exploiting the structural properties of the model, a solution algorithm based on a Dantzig-Wolfe decomposition which yields a capacitated trans-shipment subproblem along a master problem solved by the Revised Simplex method, is developed. A second modelling strategy and solution algorithm for solving the same problem is also investigated. The solution algorithm based on a combination of a Lagrangian Relaxation and period-by-period decomposition is developed and tested. The last part of the thesis is devoted to the study and implementation of a Hybrid Relaxation methodology which is incorporated in a Branch and Bound scheme for solving unit commitment problem.